Information System Strategic Planning using Ward and Peppard Methodology (Case Study: Nusatovel Salatiga) - Angelina Agnes; Agustinus Fritz Wijaya (Universitas Bina Darma, 2020)
In the current era of globalization, IS and IT are utilized to be able to compete and increase company productivity. Information system strategic planning is one of the keys in achieving the target expected by the company. NUSATOVEL PT has implemented an information system, but there are still some parts that have not implemented the information system. The information system strategy planning model uses the Ward and Peppard method with SWOT analysis, Value Chain analysis, and Mc Farlan's Strategic Grid. By using this method various factors that affect the company, both internal and external are analyzed to get a formula that is the basis for preparing a new IS / IT strategy in the form of an IS / IT portfolio, which can then be used as a strategic plan. Research using this method makes strategic planning for IS / IT that can provide recommendations or solutions to the development and implementation of IS / IT that is more effective and efficient for the company. The proposed information system strategy, namely Graphic Design SI, Customer Relations Manager SI, SI Services, can be implemented within the next 3 (three) years.